Box–Behnken design for the optimization of nanoscale retrograded starch formation by high-power ultrasonication. (April 2016) - Ding, Yongbo; Zheng, Jiong; Xia, Xuejuan; Ren, Tingyuan; Kan, Jianquan
Abstract: A new and convenient synthesis route using high-power ultrasonication combined with water-in-oil miniemulsion cross-linking technique was used to prepare cross-linked nanoscale retrograded starch (RS3). A four-factor Box–Behnken design and optimization was used to minimize particle size through the developed nanoscale RS3 based on 29 different experimental data obtained in a batch study. Four independent variables, namely, ultrasonic power (100–500 W), sonication time (40–200 min), starch content (0.5 g/100g–2.5 g/100 g), and oil/water ratio (4:1–12:1), were transformed to coded values, and a quadratic model was established to predict the responses. Variable optimization for minimizing particle size by high-power ultrasonication was performed using the quadratic model. The predicted minimized Z-Ave (611.7 nm) under the optimum conditions of the process variables (ultrasonic power, 231.52 W; sonication time, 85.19 min; starch content, 1.1 g/100 g; and oil/water ratio, 9:1) was very close to the experimental value (606.2 nm) determined in the batch experiment. SEM observation revealed that the surface of the nanoscale RS3 appeared to be progressively broken down and eroded. XRD analysis indicated that ultrasonication destroyed the crystalline structure of the clustered amylopectin and apparently led to amorphous or low-crystallinity RS3 nanoparticles. Highlights: Ultrasonication combined w/o miniemulsion produced nanoscale RS III about 600 nm. Ultrasonic power, sonication time, starch content, and oil/water ratio. Box-Behnken design including CCD and RSM. The optimum variables were 231.52 W, 85.19 min, 1.1%, and 9:1. The predicted Z-Avel (611.7 nm) was close to the experimental value (606.2 nm).